Infectious Diseases and Methods of Manage it within the Internal Medicine departments - Case study - Shifa Medical Complex - El-ramlawi, Ahmed Hamdi; Hemaid, Labeeb Abed Badia; El-Ashgar, Nizam M. (Journal of Risk and Crisis Management, 2019)
The study aimed to identifying methods and ways of managing infectious diseases and controlling infection within the Internal Medicine departments in Shifa Medical Complex and working on improving them on scientific and practical bases , Due to the importance of the study and the attempt to collect all data, a descriptive and analytical approach was adopted in order to reach the results of the study, Where the researchers made several field visits within the corridors of the Internal Medicine Hospital departments in order to know the ways of management of infectious diseases and deal with them, and was the work of several interviews with stakeholders and competence in subject of the study, Accordingly, the study reached many results and the most important is: The level of awareness and scientific and practical knowledge of health staff about management of infectious diseases and infection control in the event of a pandemic or disease is not at the required level, This is due to the lack of experience and adequate knowledge to manage infectious diseases and the lack of available resources, It was found that most of the obstacles that hinder infectious disease management process is: The acute shortage of necessary protective equipment, supplies and tools, The design of the internal environment of the Internal Medicine departments is not suitable for the management of infectious diseases but contributes to their spread, and lack of a clear protocol for proper handling of infectious diseases, Accordingly, a set of recommendations was developed based on the findings of this study and the most important is: conducting scientific and practical training and educational courses periodically specializes in the field of infectious disease management and infection control for all health staff within the hospital departments, Providing an appropriate working environment that contributes to reducing the spread of infection.